Development and application of ultra-bright laser and harmonic XUV sources - Key, M; Barbee, T; Blyth, J; Burnett, K; Cairns, G; Dangor, A; Ditmire, T; Djaoui, A; DaSilva, L; Demir, A; Dyson, A; Fews, A; et al. (1996)
Experimental work with high intensity lasers at the Rutherford Appleton Laboratory has led to the production of both XUV laser and XUV harmonic sources with extreme brightness. In particular an efficient XUV laser source has been developed based on collisionally excited neon -like Ge XXIII(J=0-1) at 19.6 nm using the high power glass laser Vulcan generating 75 ps pulses. With Vulcan operating in sub -ps CPA mode, extremely powerful and short wavelength XUV high harmonic sources have been obtained by irradiation of solid targets and recombinant laser action with high gain has been demonstrated with fibre targets. An ultra-bright Krypton-fluoride laser system, Sprite(recently upgraded to a new configuration Titania) has produced the shortest harmonic wavelength (6.7 nm) and has been used to assess the possibilities of optical field ionised recombinant laser action with gas jet targets. The Ge XUV laser has been successfully applied in fusion research for radiographic measurements of the effect of laser speckle on the hydrodynamic stability of laser accelerated thin foils. The present status of the work, the comparative performance of the XUV laser and harmonic sources and near-term future directions are reviewed.